2010
DOI: 10.1002/glia.21036
|View full text |Cite
|
Sign up to set email alerts
|

A homologous form of human interleukin 16 is implicated in microglia recruitment following nervous system injury in leech Hirudo medicinalis

Abstract: In contrast to mammals, the medicinal leech Hirudo medicinalis can completely repair its central nervous system (CNS) after injury. This invertebrate model offers unique opportunities to study the molecular and cellular basis of the CNS repair processes. When the leech CNS is injured, microglial cells migrate and accumulate at the site of lesion, a phenomenon known to be essential for the usual sprouting of injured axons. In the present study, we demonstrate that a new molecule, designated HmIL-16, having func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 57 publications
5
40
0
1
Order By: Relevance
“…The optimal effect was observed by using 8 μl of r Hm C1q supernatant while a higher amount (15 μl) caused a decreased migration of the microglia. This effect is a characteristic of cytokines having chemotactic activity and has been described for other chemoattractant factors of leech CNS conditioned medium [22]. Of interest, similar dose-dependent results were obtained by using purified r Hm C1q (data not shown).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The optimal effect was observed by using 8 μl of r Hm C1q supernatant while a higher amount (15 μl) caused a decreased migration of the microglia. This effect is a characteristic of cytokines having chemotactic activity and has been described for other chemoattractant factors of leech CNS conditioned medium [22]. Of interest, similar dose-dependent results were obtained by using purified r Hm C1q (data not shown).…”
Section: Resultssupporting
confidence: 82%
“…Nerve cells, neurons and microglial cells were mechanically resuspended by gentle scraping (total nerve cells). After a filtration through 7 μm nylon mesh as described [17,22], the enriched microglial cell population was then collected and centrifuged at 1,000 g for 10 minutes at RT. The cell pellet was resuspended in L-15 medium (100 μl per nerve cord) for migration assays.…”
Section: Methodsmentioning
confidence: 99%
“…A high dose inhibition of chemotaxis is characteristic of chemokines [10] and is consistent with the inhibitory effect recently described for other chemoattractant factors in the leech central nervous system. [36,37] The results also showed that the different concentrations of IL-8 did not influence the types of cells migrating into the MG. Ultrastructural analysis using scanning (SEM, Figure 2E-G) and transmission (TEM, Figure 2H-J) electron microscopy showed that the MG pellets were infiltrated by cells characterized by a cytoplasm containing numerous small highly electron-dense granules ( Figure 2F and 2I) and by cells showing an electron-dense cytoplasm containing a few large granules ( Figure 2G and 2L). These two types of cells can be found both strictly associated with each other or isolated ( Figure 2E and 2H).…”
Section: Light and Electron Microscopic Examination Of Mg Pellets Supsupporting
confidence: 56%
“…It is a potent chemoattractant and also has a regulatory function in the induction of cytokines including IL-6, TNF-α, and IL-1β [26] . IL-16 is produced by microglia in response to CNS injury and, in turn, activates microglial migration to the site of injury and repair [27] . Following ischaemic infarction, it reacts with CD4+ receptors and activates T cell migration, through the up-regulation of receptors such as T cell CD25 and MHC class 2 molecules.…”
Section: Discussionmentioning
confidence: 99%